THE PLACE OF TRADITIONAL MUSICAL CULTURE IN THE MODERN WORLD: CHALLENGES AND QUESTIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses some features of traditional music and its carriers that distinguish it from academic and all other types of art. What is the fate and meaning of traditional art and what can be done to keep it alive and developing? The problem of the content and form of traditional art is considered. Both in traditional art are very different from the types of art known to modern culture. The content of traditional art is not thematic or informational, it is rather a channel connecting the listener with the intangible world, and therefore it is inexhaustible. The form of traditional art, being oral, intangible, is transmitted only through the performer and then thanks to tradition.
Keywords: traditional music, carriers, content and form, intangible cultural heritage.